Developing an Accessibility Metric for VR Games Based on Motion Data Captured Under Game Conditions - Thiel, Felix J.; Steed, Anthony (Frontiers in Virtual Reality, 2022)
Virtual Reality (VR) games are not as accessible as conventional video games because they heavily rely on the motion of the body as the main means of input. This causes large accessibility issues because it prevents some physically impaired players from using them. It also makes it more difficult to develop accessibility tools to address the issues. Given these challenges, it is of particular importance that an impaired player can determine whether they will be able to play a game before they buy it. We propose the first prototype of a metric that aims at visually presenting the important aspects of the body motion that a game requires. Instead of manual classification, the metric is based on data captured from able-bodied players that play the game as designed. In this work, we introduce the metric itself, demonstrate how it differentiates six popular VR games based on data we collected in a user study, and discuss limitations and routes for further development.